Demographic, socioeconomic and functional health-related factors in the selection of vaginal pessaries used for the conservative treatment of pelvic organ prolapse: a retrospective study - Orsolya Oláh; Miklós Romics; Nándor Ács; Richárd Cseh; Péter Nyirády; Attila Majoros (BMC Women's Health)
Abstract Background Vaginal pessary therapy is a well-known conservative treatment of pelvic organ prolapse (POP). According to several national guidelines, pessary therapy should be used as a first-line treatment for pelvic organ prolapse. A distinction is made between pessaries that can be worn permanently or require daily control. This therapy is primarily chosen by elderly patients who are not suitable for surgery or by patients not wishing to undergo surgical treatment. The aim of our study was to investigate what demographic, socioeconomic and functional health-related factors play a role in the choice of the pessary types, and to provide healthcare professionals with guidance on recommending a pessary type to patients based on these factors. Methods 115 female patients using vaginal pessaries for POP were included in our study (group I:73 pts used a daily control “cube” pessary (DCP), group II.:42 pts used a long-term wear ring pessary (LTP). Data collection was performed between March 2021 and March 2022 through a personally completed questionnaire or telephone interview. The following factors were investigated: patients’ age, fertility, education level, employment status, marital status, independence, hand function, vision, mobility, physical and sexual activity. Results A significant difference was found between the DCP and LTP groups in terms of average age (44.9 vs. 75.7 years p < 0.0001), fertility (61.6 vs. 4.6% p < 0.0001), employment status (retired: 18 vs. 100% p < 0.0001), marital status (single: 8.3 vs. 44.1% p < 0.0001) and educational level (highest: 81.9 vs. 25.6% p < 0.0001). In terms of functional health-related factors, such as weakened hand function (1.4 vs. 34.9% p < 0.0001), vision impairment (19.4 vs. 58.1% p < 0.0001), reduced mobility (5.5 vs. 81.4% p < 0.0001), sexual activity ratio (87.5 vs. 0% p < 0.0001), and the level of physical activity (VAS: 9.5 vs. 6.1 p < 0.01) also significant differences were registered between the DCP and LTP groups. Conclusions The choice of the type of vaginal pessary treatment for POP is influenced by many patient-side factors. Trial registration The study was conducted with the approval of the Regional Institutional Scientific and Research Ethics Committee of Semmelweis University (SE RKEB 97/2022).